Optimizing Parental Involvement in Addressing Addictive Gadget Use Behavior in Elementary School Children - Ni Putu Anmanda Dewi; Luh Suci Apriliani; Kadek Puja Hapsari; Komang Mila Kusuma Sari; Ketut Reza Natasya Putri (Jurnal Pendidikan Guru Sekolah Dasar, 2026)
Without proper supervision, elementary school children's device use can affect their behavior, learning styles, and development. This study used a literature review of research conducted between 2021 and 2026 on the role of parents in children's device use. The purpose of this study was to analyze the optimization of parental involvement in children's device use based on previous research. The results of this study indicate that parents need to be supervisors, guides, and good role models for their children in device use so that children can behave adaptively towards technology. Therefore, the role of parents is crucial in fostering healthy device use behavior in children.